Pelatihan Pelaporan Keuangan dalam Peningkatan Kualitas Laporan Keuangan bagi Pelaku Usaha UMKM - Syamsul Alam; Nuramal Nuramal; Resky Arianti Akob; Muh. Irwan Nur Hamiddin; Chairunnisa Rumianti; Sitti Masyita; Darmawati Darmawati; Heslina Heslina; Faisal P; Nasrul Nasrul (Lembaga Pengembangan Kinerja Dosen, 2024)
This financial report preparation training activity aims to remind MSME business actors of their ability and knowledge in compiling financial reports. This activity is to respond to the difficulties of business actors that they have encountered so far. Inability and ignorance in compiling financial statements make it difficult for them to analyze their financial performance. This training activity lasted for 3 days where the material was carried out by conducting training in the preparation of financial reports then continued with the practice of making financial reports and finally continued with assistance by the team formed for this activity. This activity was attended by 15 MSME actors in Sanrobone village, Takalar. Based on the results of the activities that have been described, the conclusion of community service activities about financial reporting training in improving the Quality: MSME Financial Reports in Sanrobone Village, Sanrobone District, Takalat Regency is as follows: This activity aims to increase the understanding of financial reporting in improving the quality of financial reports for MSME actors. This training activity provides benefits in increasing productivity for MSME actors. The follow-up of activities is expected to be more about continuous training techniques and mentoring for MSME actors